Silica-based materials for advanced chemical applications - Pagliaro, Mario, 1969- (RSC Pub., 2009)
This clear and concise book is the first to address the hot topic of functional silica gels and their applications. This is the first book to address the hot topic of functional silica gels and their applications. Originally used mainly in chromatography, specialized silica gels have evolved into crucially important functional nanomaterials suitable for use in, amongst other things, chemical synthesis, analysis, purification, surface protection and drug release. It is estimated that the world's current 1 billion dollar market for sol-gels (mostly silica-based) will grow by more than 5% per year from 2006 to 2011. Actually, as many revolutionary products are now reaching the market, it will increase much faster. Commercial applications include glasses, paints, catalysts and fragrances. Medical uses include the delivery of vitamins, hormones and acne treatments and the synthesis of the powerful anticancer drug, taxol. Sol-gel technology also forms the basis of the MetaChip, thanks to which potential new drugs can be identified rapidly and simultaneously. With content relevant to both scientific and commercial viewpoints, the book will interest researchers and undergraduates as well as managers and consultants in the chemical industry. Those from an industrial background will gain a clear picture of what this technology is all about and how it can be used to solve their specific problems. All readers will benefit from the clear, concise style and consistent treatment of topics. The book demonstrates how chemists synthesize, from the bottom-up, tailor-made (nano)materials of immense practical importance spanning the fields of chemistry, physics, materials science, engineering, biology and medicine. It also shows how the versatility of silica gels results from their physical and chemical properties. An updated outlook on new commercial products, and the companies which make them, greatly adds relevance and practical value to the text.
Keywords: Silica gel.; Nanostructured materials.; elektronické knihy; electronic books